Assessment of Sulfur Dioxide Levels in Atmospheric Air Over the Period 2019–2024 - Drygval, Anna; Drygval, Polina; Tabunshchik , Vladimir (Civil Engineering Journal, 2025)
This study investigates the spatiotemporal distribution and dynamics of atmospheric sulfur dioxide (SO₂) over the Crimean Peninsula during the period 2019–2024, employing protected natural areas as background reference sites for air quality assessment. The primary objective is to determine the variability in SO₂ concentrations in the atmosphere over Crimea. Methodologically, the study involves selecting background sites across diverse landscape levels throughout the peninsula, and applying Z-analysis to categorize ambient air pollution into four levels: conditionally low, average, elevated, and high. The analysis encompasses annual mean SO₂ levels, assessment of temporal trends, and localization of pollution hotspots. Results indicate a peak in SO₂ levels in 2020, predominantly at mid-mountain landscape level, and a minimum in 2019. Overall, a decreasing trend of 25.4 µmol/m² per year in SO₂ concentrations is observed, despite localized zones of high pollution, including areas northeast of the regional center, Simferopol. In 2022, the low-mountain landscape level of the northern macroslope exhibited the most extensive conditionally high pollution zone, covering nearly half of its territory. The novelty of this work lies in integrating protected natural areas as reference sites within the Z-analysis framework, enabling more precise identification of anthropogenic influences and the spatial distribution patterns of sulfur dioxide concentrations in the region’s atmosphere.